SOCIALIZATION OF THE USE OF THE CANVA APPLICATION AS A HEALTH PROMOTION MEDIA AT RSIA DR. HJ. KARMINI TASIKMALAYA CITY - Prabowo, Tony; Junaedi, Fadil Ahmad; Hermawan, Randy (Universitas Bakti Tunas Husada, 2024)
In today's increasingly advanced digital era, digital media is an effective means of conveying information to the public. One very popular application for creating graphic designs is Canva. Canva is a platform that allows users to create visually appealing and professional designs without the need to have deep design skills. In the context of hospitals, Canva can be used as a tool to create health promotion materials in hospitals that are attractive and easy to understand such as creating posters, flyers, brochures, infographics, so as to convey important messages about health to public patients. The purpose of this socialization is to explain the targets that can be used in health promotion, introduce the Canva application in health promotion and determine social media that will be used as health promotion media. The method used is the method by giving lectures and discussions on increasing health promotion knowledge in hospitals. Thus, the results of health promotion efforts at RSIA dr. Hj. Karmini can be one of the effective strategies in improving overall public health so that social media can play an important role in promoting hospitals by utilizing platforms such as Facebook, Instagram, and Tiktok.Keywords: Socialization, Promotion, Canva, Social Media.